THE GLOBAL WATER “CRISIS” SEEN BY PERSPECTIVE OF THE POLITICAL GEOGRAPHY - Bordalo, Carlos Alexandre Leao (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2012)
In this beginning century the Unit Nation Organization has held three Water World Forum (Kyoto, 2003, Mexico City, 2006, Istanbul, 2009) where wars were fought in paradigms. The water as a universal human right versus water as a commodity, and an imminent crisis for the supply of fresh water even in this century. These are issues that should be analyzed by all, and here we present a perspective of political geography, a reflection about the global water crisis that is? Where we will see that it is not a crisis of availability of fresh water, but the crisis of unequal access to water, as well as, in different forms of use and consumption, such as the disparately between rich and poor countries.